Advanced atomic layer deposition: metal oxide thin film growth using the discrete feeding method. Issue 4 (21st December 2022) - Park, Jae Chan; Choi, Chang Ik; Lee, Sang-Gil; Yoo, Seung Jo; Lee, Ji-Hyun; Jang, Jae Hyuck; Kim, Woo-Hee; Ahn, Ji-Hoon; Kim, Jeong Hwan; Park, Tae Joo
Abstract : A HfO2 film was grown using discrete feeding ALD, an advanced ALD process designed to improve the surface coverage of the precursor, which decreased the residual impurities in the film and increased the film density. Abstract : A HfO2 film was grown via atomic layer deposition (ALD) with a discrete feeding method (DFM), called DF-ALD, and its physical, chemical, and electrical properties were studied. In conventional ALD processes, even in the growth saturation condition, not all substrate surface reactive sites react with precursor or reactant molecules because physisorbed precursor and byproduct molecules screen the subjacent surface reactive sites. The DF-ALD process in this work employed divided precursor feeding and purging steps in the growth saturation condition of a control ALD process, such that the divided steps efficiently eliminated the physisorbed precursor molecules or by-products screening the subjacent surface reactive sites. This increased the adsorption and filling efficiency of the precursor molecules onto the substrate or film surface during deposition. As a result, the DF-ALD increased the film density and reduced the interfacial layer thickness which degrades the electrical properties of a high-k dielectric, and reduced impurities in the HfO2 thin film.